Transformational Leadership in Developing Student Character through Extracurricular Activities: A Case Study in an Indonesian Elementary School - Jamaludin; Inaya Sari Melati (Educational Management, 2025)
The purpose of this study is to construct a model of principal leadership in developing student character through extracurricular activities in resource-limited elementary schools. The method used was qualitative with an intrinsic case study design at SD Negeri Mendala 01, Brebes. Data were collected through in-depth interviews, participatory observation, and documentary studies, then analyzed interactively. The results show that: (1) The principal's transformational leadership demonstrated through exemplary behavior, inspirational vision, teacher empowerment, and clinical supervision is the main driver of the character ecosystem; (2) Extracurricular activities (Scouting, Volleyball, Arts, Theater, Painting) function as a "field of practice" and "living laboratory" that integrates Lickona's character education trilogy (moral knowing, feeling, action) through experiential learning; (3) A transformational impact is evident in the significant improvement of student character (such as discipline, responsibility, self-confidence, cooperation, creativity, patience), proven by the transfer of values to academic and home contexts, and a shift in school culture towards greater collaboration and value orientation. In conclusion, this study reconstructs a synergistic character development ecosystem model, driven by transformational leadership and effectively mediated through value-based extracurricular activities.